FINANCIAL PERFORMANCE ASSESSMENT OF TELECOMMUNICATIONS SECTOR COMPANIES - Narwiyah Narwiyah; Nur Fatma (Entrepreneurship Undergraduate Program at Amkop Business School, 2026)
This study looks at financial reports utilizing analysis, specifically liquidity ratios, solvency ratios, activity ratios, and profitability ratios, in order to examine the financial performance of telecom businesses listed on the Indonesian stock exchange between 2020 and 2022. This approach focuses on the financial performance of the organization using both quantitative and descriptive analysis techniques. Secondary data in the form of income statements, balance reports, and data required from 2020 to 2022 are the kind and source of data used. The data is derived from reports of telecoms financial businesses that are listed on the Indonesia Stock Exchange. Research indicates that PT.XL Axiata and PT.Telkomsel perform better. Good liquidity ratios, solvability ratios, activity ratios, and corporate profitability ratios each year serve as proof of this.Keywords: Telecommunication, company, Financial Performance, Financial Ratios